ANALISIS KETERAMPILAN BERPIKIR TINGKAT TINGGI SISWA SD PILOT PROJECT KURIKULUM 2013 KOTA SEMARANG - Khusnul Fajriyah, Ferina Agustini (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2018)
The implementation of the 2013 curriculum continues on pilot project schools on consideration of readiness. The 2013 curriculum is expected to facilitate the development ofstudents' thinking skills to a higher level through a scientific approach. This study aims toobtain detailed data about how the ability of students of pilot project elementary school inSemarang city in applying high-level thinking skills in accordance with competence. Theresearch design used is descriptive quantitative which is directed to describe student's highorder thinking skill through calculation of score, mean, percentage. The results show thathigh-order thinking skills of elementary school students of the 2013 Curriculum pilot projectare in the category ‘minus’ with an average score of 40. The student’s ability to classify an dinduce is at level ‘enough’. While the ability of deduction, error analysis, perspectiveanalysis, decisions making, experiences, solving problems of the discovery which is obtainedby students are at level ‘low’.Keywords: Higher Order Thinking Skills (HOTs), elementary school students